(untitled) (Latakia University Journal -Medical Sciences Series, 2024)
Sugammadex, a new modified gamma cyclodextrin, reverses the neuromuscular blockage induced by rocuronium by forming a strong complex with this muscle relaxant. In order to evaluate possible interactions with potentially co-administered drugs, the interaction between sugammadex and propranolol was investigated using three different methods; the affinity capillary electrophoresis (ACE) method coupled to an ultraviolet (UV) detector, the affinity capillary electrophoresis method coupled to fluorescence detector and Fluorimeter, for the first time. Using ACE, changes in the effective mobility of guest drug were correlated with the increasing concentration of the host molecules in background electrolyte (BGE). Using Fluorimeter, changes in the fluorescence intensity of guest drug were correlated with the increasing host concentration in sample solution. Detected changes were successfully fitted into a nonlinear curve equation; assuming 1:1 stoichiometric interaction. The calculated association constants (Ka) were: 4137 M-1, 4215 M-1and 4110 M-1 using three methods as mentioned above; respectively. These values confirm the affinity strength of the predicted inclusion complex between sugammadex and propranolol.